1999
DOI: 10.1212/wnl.52.7.1417
|View full text |Cite
|
Sign up to set email alerts
|

The effect of estrogen replacement on early Parkinson’s disease

Abstract: We found a positive association between estrogen use and lower symptom severity in women with early PD not yet taking L-dopa. These results indicate that estrogen therapy should not be avoided and may be beneficial in early PD, at least prior to the initiation of L-dopa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
155
2
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(164 citation statements)
references
References 20 publications
6
155
2
1
Order By: Relevance
“…A number of differences in nigrostriatal DA response to estrogen have been reported as a function of the time/duration of estrogen exposure (Hruska 1986;Fernandez-Ruiz et al 1989), the differential site of 6-OHDA administered or the dose of 6-OHDA used (Ferraz et al 2003). It is worth noting that a retrospective chart review showed that estrogen might be beneficial in early PD, at least prior to the initiation of L-dopa (Saunders-Pullman et al 1999). In our present study, we chose the lowest efficient dose of EB for detecting the possible effects of estrogen on the amygdala of PD model rats.…”
Section: Discussionmentioning
confidence: 99%
“…A number of differences in nigrostriatal DA response to estrogen have been reported as a function of the time/duration of estrogen exposure (Hruska 1986;Fernandez-Ruiz et al 1989), the differential site of 6-OHDA administered or the dose of 6-OHDA used (Ferraz et al 2003). It is worth noting that a retrospective chart review showed that estrogen might be beneficial in early PD, at least prior to the initiation of L-dopa (Saunders-Pullman et al 1999). In our present study, we chose the lowest efficient dose of EB for detecting the possible effects of estrogen on the amygdala of PD model rats.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, postmenopausal estrogen treatment has been reported to retard PD progression [645,646]. A small case-control study reported increased risk of PD associated with hysterectomy (OR 3.36, 95% CI 1.05-10.77), but no associations for age at menopause or use of postmenopausal estrogens [647].…”
Section: Estrogenmentioning
confidence: 99%
“…17␤-estradiol was reported to protect against NMDAinduced excitotoxicity by direct inhibition of NMDA receptors (Weaver et al 1997) and recently, a positive association was reported between estrogen use and a lower symptom severity in women with early Parkinson disease no yet taking L-Dopa (Saunders-Pullman et al 1999).…”
Section: Nmda Receptors Mrna Levelsmentioning
confidence: 99%